A Dyadic Model of Customer Orientation: Mediation and Moderation Effects. (16th December 2013) - Brach, Simon; Walsh, Gianfranco; Hennig‐Thurau, Thorsten; Groth, Markus
<x xml:space="preserve">Abstract</x> This research distinguishes between employees' customer orientation (ECO) and customer orientation as perceived by customers (COPC) to investigate the contingencies of the relationship between these two constructs. Drawing on emotional contagion theory and using a dyadic field study design, the authors examine whether ECO affects COPC, as well as whether the link between ECO and COPC might be mediated by employees' authentic emotional displays. They also examine service scripts and the accuracy with which customers detect employees' authentic emotional displays as moderators of this mediated link. The findings confirm the important role of ECO as an influence on COPC and provide evidence that employees' authentic emotional displays mediate the effects of ECO. In addition, service scripts and customers' detection accuracy have moderating effects.